A review of geospatial technologies for improving Marine Spatial Planning: Challenges and opportunities. (1st January 2023) - Schwartz-Belkin, Inbar; Portman, Michelle E.
Abstract: Common marine spatial planning challenges include lack of data on the marine environment, high mobility of both animals and humans, and plan implementation challenges including lack enforcement and compliance with regulations along with monitoring deficiencies. These can be potentially addressed using geospatial technologies (GTs) such as remote sensing, GPS and GIS. This research presents geospatial tools that are available for the process of developing, implementing, and monitoring marine spatial plans. Tools include satellites and water-based platforms carrying various sensors and receivers for environmental ocean data, vessel tracking and animal telemetry via multispectral, acoustic, radar, and other means. Planners and ocean managers might not always be aware of technological solutions available for the development and implementation of marine spatial plans. Here, urgent planning needs, summarized from various publications, are linked to GTs solutions published in relevant literature between the years 2015–2020. The GTs were used for data collection, dynamic human activities' management, environmental monitoring and enforcement, all as required by marine spatial plans. This paper concludes with insights into GT solutions that can enhance the process of evidence-based management and spatial planning in marine environments. Highlights: Common MSP challenges identified for generic steps in the MSP process. Evidence-based literature review identifies geospatial technologies solutions to MSP challenges. Guidelines for utilizing geospatial technologies in MSP practices are suggested.